2021
DOI: 10.18203/2349-2902.isj20214752
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation and management of scrotal swelling

Abstract: Background: The present study was conducted with the main purpose to identify the mode of presentation, various treatment modalities and outcome of these with their complications.Methods: This prospective study was carried out on a total of 100 subjects presented with scrotal swellings. Exhibiting symptoms were noted including discomfort, painless swelling, urine symptoms and fever. Questionnaires were used to analyse all the predisposing factors of patients, which were then categorized as idiopathic, urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Testicular torsions when diagnosed early within six hours can be managed by exploration and orchidopexy. [10][11][12] In our study, maximum number of cases were observed in the age group 18-28 years were 32 (35.56%), followed by 28-38 were 29 (32.22%) and were 38-48 years 13 were (14.44%), followed up by 48-58 years were 6 (6.67%), 58-68 years were 7 (7.78%) and 68-78 years were 3 (3.33%) (Table 2). In the study conducted by Chauhan et al maximum incidence of patients was in the age group of 21-30 years (41%) followed by 31-40 (18%) and 41-50 years (13%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testicular torsions when diagnosed early within six hours can be managed by exploration and orchidopexy. [10][11][12] In our study, maximum number of cases were observed in the age group 18-28 years were 32 (35.56%), followed by 28-38 were 29 (32.22%) and were 38-48 years 13 were (14.44%), followed up by 48-58 years were 6 (6.67%), 58-68 years were 7 (7.78%) and 68-78 years were 3 (3.33%) (Table 2). In the study conducted by Chauhan et al maximum incidence of patients was in the age group of 21-30 years (41%) followed by 31-40 (18%) and 41-50 years (13%).…”
Section: Discussionmentioning
confidence: 99%
“…Testicular torsions when diagnosed early within six hours can be managed by exploration and orchidopexy. [10][11][12]…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation of various hydrocele types is imperative for appropriate management and favorable perioperative outcomes. The presence of fluid brilliantly transilluminates the swelling, aiding in the differentiation from conditions such as an inguinal hernia, spermatic cord lipoma, epididymal cyst, spermatocele, testicular tumor, scrotal edema, and varicocele [5].…”
Section: Introductionmentioning
confidence: 99%